Emotional, Social, and Cognitive Intelligence as Predictors of Job Performance Among Law Enforcement Agency Personnel. Issue 2 (2nd April 2016) - Adetula, Gabriel Agboola
ABSTARCT: This study examined emotional, social, and cognitive intelligence as predictive variables to job performance of law enforcement agents. Three hundred police, prison, and court employees in Akure metropolis were randomly surveyed as sample respondents. Questionnaires and interview methods were used for data gathering. Pearson Product Moment Correlation and Multiple Regressions Statistical analyses were utilized which produced the following results. There was no significant relationship between Emotional Intelligence and Job Performance. There was a significant negative relationship between Social Intelligence and Job Performance. There was a significant negative relationship between Cognitive Intelligence and Job Performance. Emotional and Social Intelligence together had positive joint significant relationship with Job Performance (r = 0.30; p < .001). Emotional and Cognitive Intelligence had positive joint significant relationship with Job Performance (r = 0.26; p < .001). Social and Cognitive Intelligence had positive joint significant relationship with Job Performance (r = 0.61; p < .001). Results also confirmed that Emotional, Social, and Cognitive Intelligence jointly significantly predicted job performance (F (153) = 4.036; R = 0.27, R 2 = 0.75; p < .01). These findings confirmed the importance and relatedness of these variables to work. It is, therefore, paramount that police and other law enforcement authorities recognize and must select candidates who scored or possessed high qualities on emotional, social, and cognitive intelligence for organization effectiveness.